Cycle Threshold Value and Absolute Lymphocyte Count Relationship with Severity of COVID-19 - M. Alfian Agustian; Andani Eka Putra; Cimi Ilmiawati; Novita Ariani; Linosefa Linosefa (Lembaga Pengembangan Kinerja Dosen, 2025)
Coronavirus Disease 2019 (COVID-19) is a case that spread to many countries, including Indonesia, due to of SARS-CoV-2 transmission. West Sumatra, especially Padang city, is one of the highest spread of COVID-19 cases in Indonesia. This study aimed to examine the relation between Ct value and absolute lymphocyte count with the severity of COVID-19. The type of this research was analytic observational with the cross sectional study. We collected 106 patients data in Dr. M. Djamil Padang hospital from moderate to critical severity from June-August 2021. The data were collected and processed using convenient sampling which was then tested using Spearman correlation, One Way ANOVA, and Kruskal-Wallis tests. The results showed that most patients with confirmed COVID-19 were at the age of 56 to 65 years (30.2%), were women (51.9%), and had hypertension comorbidity (27.6%). We found that the median (IQR) of the Ct value is 23.5(10) and the mean ± SD of absolute lymphocyte count is 1213±56. There was a relation between Ct value and severity of COVID-19 (p=0.019), absolute lymphocyte count and severity of COVID-19 (p<0.01), and weak negative correlation of Ct value and absolute lymphocyte count (p=0.040, r=-0.200). Increasing viral load may elicit higher immune response clinically in moderate to critical COVID-19 patients.